The Archeology Field in the Mobile Era: A Roadmap to Catch-up - Khelifi, Adel Labidi (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The field of archeology is undoubtedly left behind in the mobile era compared to other scientific domains. The deployment of mobile technology solutions is of meagre contribution to the field. In fact, almost no mobile apps are designed as per archeologists’ work requirements in the excavation site. This study aims to tackle this dilemma through a roadmap to pave the way for the community to recover this digital divide. The roadmap encompasses a comprehensive methodology on how to develop mobile apps that meet the requirements of its respective audience. The development of two apps is introduced to illustrate the implementation of the methodology. The result of adopting this ‘roadmap’ study improves the data collection, processing and usage. It enhances information accuracy and sharing. Besides, it reduces the ‘destructive’ aspect of the archeology investigations and provides archeologists with handy solutions that they can use ubiquitously. The refinement of the first versions of mobile apps for archeology will make the measurements more accurate and improve the level of maturity of the field vis-à-vis the mobile technology sector. Most significantly, this study opens the door, eventually, for a new era wherein the community starts by deploying mobile technology solutions to ultimately go beyond the current dating techniques, such as the radiocarbon dating method. An ultimate future work could be the exploration of developing mobile apps, in an interdisciplinary context, that measure the age of archeological items by few clicks and prepare the field for the forthcoming post-device era.